Implementation of the Independent Curriculum in Physical Education and Health: A Qualitative Study in Public Elementary Schools of Gantung Subdistrict - Misbahudin; Soni Nopembri; Tri Ani Hastuti (Indonesian Journal of Sport Management, 2025)
Background: implementation of the Independent Curriculum in Physical Education and Health (PJOK) remains understudied, particularly in rural contexts where teacher readiness, facilities, and pedagogical support differ from urban schools. Existing research has focused largely on administrative aspects or general teacher perceptions, leaving limited understanding of how motor learning principles, character development, and contextualized physical activities are integrated into daily classroom practice. This study addresses this gap by exploring how the Independent Curriculum is enacted in public elementary schools in Gantung Subdistrict, a rural area with diverse socio-geographical conditions Methods: ualitative descriptive design, data were collected through semi-structured interviews, classroom observations, and document analysis. The study involved nine informants six PJOK teachers and three school principals focusing on curriculum interpretation, instructional strategies, assessment practices, and facility availability. Results: findings show teachers understand the aims of the Independent Curriculum but implement it only partially. Motor learning principles, such as varied practice and structured feedback, are not yet consistently applied, and character values introduced informally rather than embedded in lesson planning. Limited sports facilities and uneven instructional leadership further constrain curriculum enactment. Teachers often rely on traditional activities due to restricted resources, while principals’ support varies across schools. Conclusion study concludes that effective implementation requires strengthened teacher competence in motor learning pedagogy, improved integration of character education, enhanced basic facilities, and stronger school leadership. Theoretically, research contributes by linking motor learning and curriculum implementation in rural PJOK settings. Practically, it offers recommendations for teacher training and school-level policy improvements tailored to rural conditions.